Collaborative teacher professional development in schools in English (UK) and Shanghai (China): cultures, contexts and tensions. Issue 3 (3rd April 2019) - Zeng, Yan; Day, Christopher
ABSTRACT: This mixed method research explores the contexts, purposes, forms, practices, and effects of school provided collaborative professional development (PD) as experienced by teachers working in primary and secondary schools in England and Shanghai. The research is part of a larger partnership pilot study by the University of Nottingham and Shanghai Normal University, which focused on opportunities for and experiences of participation in formally organized professional development, using as a point of departure the findings of the Teaching and Learning International Survey (TALIS) 2013 report of teachers' perceptions of their professional development. Given the differences between the two jurisdictions in their PISA ( Program for International Student Assessment ) rankings, and between national cultures, teacher expectations and conditions of work, professional development purposes, forms and practices in schools might be expected to differ. The research found that there was a similar emphasis in both jurisdictions upon 'functional' rather than 'attitudinal' oriented professional development, but that teachers in Shanghai schools experienced more of the latter than those in the English schools studied. Such differences in the relative emphasis between the two jurisdictions upon the 'attitudinal', challenge the benefits of focusing collaborative professional development primarily upon the 'functional' in English schools.